Um panorama de artigos sobre a aprendizagem do cálculo diferencial e integral na perspectiva de David Tall - Almeida, Marcio Vieira de (2013)
The focus on this research is the learning and teaching of Differential and Integral Calculus, through the reading of articles written by the researcher David Tall. It is a bibliographical theoretical research, in the modality of panorama, in which the organization is also based on elements of Content Analysis, according to Bardin. We present information about the biography of the English researcher and his relationship with the community of national research. The CAPES Thesis Database was studied, with the objective of identifying the use of theories developed by Tall in national researches. The material for analysis, used for the development of the panorama, was based on 14 articles, taken from the session Limits, Infinity & Infinitesimals of the academic website of the English researcher. The theoretical elements and the approaches in teaching formulated to the concepts real numbers, infinity, limits, continuity, derivatives, integral and differential equations are highlighted in this material. The panorama brings summaries and analysis of theoretical elements, besides highlighting important information on the learning and teaching of Differential and Integral Calculus under Tall s perspectives. With this research, we hope to have contributed to both research and teaching practice